NAMA, PENEMPATAN DAN MAKNA UKIRAN TRADISIONAL MINANGKABAU RUMAH GADANG SICAMIN KABUPATEN AGAM - YURINO JOANSA, Drs. Efrizal, M.Pd, Drs. Abd. Hafiz,M.Pd (Serupa The Journal of Art Education, 2015)
The purpose of this study is to describe the name, placement and meaning of Minangkabau traditional carvings on the walls of rumah gadang Sicamin. This research is qualitative method. Research done by observations, interview, and documentation. Data analysis done by collecting data, reducing data, presenting data and drawing the conclusion. validity of data tested with triangulation techniques. The study found that there are 30 names carved of 40 shapes carved, later found 25 meaning carvings of 30 names carved. These carvings were made in 1405 in large and small fields, placed vertically, horizontally and diagonally on the wall rumah gadang Sicamin, except the rear wall rumah gadang.Kata kunci : ukiran, rumah gadang Sicamin